RAFIN’S SNACK WIRAUSAHA LOKAL GO INTERNATIONAL - Nurbaiti, Nurbaiti; Yopita, Yopita (Jurnal Bakti Masyarakat Manajemen, 2023)
The snack food industry is currently one of the industries that provides great prospects in Indonesia and abroad. To more understand the production process, product innovation, and marketing strategies used by Rafin's Snack, the aim is to provide in-depth insight into the company's operations, as well as identify best practices that can be applied in the snack food industry. The emergence of various snack brands in the Indonesian market reflects the high consumer demand for convenient and tasty snacks. Rafin's Snack was established with the aim to answer this challenge, presenting snacks that are not only delicious but also reflect Indonesia's rich culinary culture. Rafin's Snack was founded in 2020 by a group of young entrepreneurs who had a vision to introduce the flavors of Indonesia through innovative snacks. However, most of the existing products still lacked attention to health aspects and the uniqueness of local flavors. Learn industry practices, collect data, and gain practical insights relevant to students' studies. Students will get the opportunity to connect the theory learned with real practice, while the management team can discuss and learn from the business strategies implemented by Rafin's snack towards more widespread trade abroad in an effort to enter the international market.